APPLICATION OF THE WP METHOD AS A DETERMINATION OF THE NEW MEKAR VILLAGE ASSISTANCE (Jurnal Ipteks Terapan, 2023)
Mekar Baru Village is a village located on Petatal Plantation Street, Datuk Tanah Datar District, Batu Bara Regency, North Sumatra 21254 which has a fairly large population, of which this village has 7 hamlets in one village. The problems that exist in Mekar Baru Village are in determining the acceptance of village assistance which is difficult to determine, because the number of aid proposals that propose more proposals that come in, this is very troublesome for village officials who choose to receive assistance. As the problem develops, a decision support system is needed. A decision support system is a system to find support for decisions taken using a system designed based on user needs in helping to make decisions, designed based on predetermined criteria and alternatives and has a structured and programmed system in the form of weighting that will be accumulated and normalized and produce a ranking.